IMPROVEMENT OF WEAR-RESISTANCE AND SERVICE LIFE OF MULTI-DISK BRAKE MECHANISMS OF «BELARUS» TRACTOR BY LASER THERMAL HARDENING OF FAST WEARING PARTS - O. S. Kobjakov; N. V. Spiridonov; A. A. Barkun (Наука и техника)
Problems concerning wear resistance improvement of «Belarus» tractor brake mechanism parts are considered in the paper. Properties of ВЧ-50-pig iron are investigated as a result of laser thermal hardening by various technological methods.